Percepção da família ao abandono afetivo da pessoa institucionalizada - Steiger, Leandro (2018)
The human ageing has been extensively discussed in the society, either with experiences to cure diseases, extension of years of life, the possibilities that each human being has to enjoy a dignified life. There is an increase of long stay institutions as well as an increase in modern elderly institutionalization. This phenomenon, nowadays, has among its foundations the norms of the state, which, foresee the assurance of the elderly rights, shared between Family, Society and State. This study had as purpose to learn about the culture of care, in modernity discussing emotional abandonment and the rupture of family bonds, which, for more than a year have no contact with the institutionalized elderly person. The region of coverage of this study is in the Northwest Frontier and Celeiro of the Rio Grande do Sul estate. It was necessary to know the joining process of the elderly person in the long stay institutions; understand how the relationship of the family and the elderly person is, regarding the bonds maintenance. With a semi-structured research instrument, it was possible to carry out and identify visits in organizations and interviews with managers, technical team and mainly, to interview the relatives that have no contact with the elderly person. The study also provided to know about the involved factors in the family distance regarding the institutionalized elderly person when they join the long stay institutions, being this an opportunity to comprehend the families‟ situations, the possibilities, the bounds, no judgment about the estrangement. In addition, the reflection about the stigma of the family‟s responsibilities decrease when the elderly person is institutionalized, it means, to focus on the bonds ruptures and the emotional abandonment as something to work on, constantly invested with the society organization. Previously, it is possible to consider that the long stay institutions need to realize partnerships with the Public and Private Organizations to keep qualified information regarding the residents. To simplify the contact between families, to keep a qualified professionals team and a bigger view of the different situations, what demands time and investigative work. The institution, the related cases to work, basically had their joining enabled by the Social Assistance of the Municipalities Secretariats, because from the three analyzed cases, lastly, remained that there are oversights situations, domestic violence, associated with the social reality and family relationships. Even though, we can see the necessity of a better viability of the Social Politics intended to the assurance of the elderly rights, since avoiding the emotional abandonment and the rupture of family bonds as well as finding alternatives, so that people, the citizens, can give a new meaning to the experienced situations in the family nucleus and notice the reflection possibilities regarding the oversights resulting from other generations and sometimes replicated in family contexts, however, there is space for the oversights ruptures.